RE-DESIGN SISTEM SANITARY KAPAL PENUMPANG KAPASITAS 500 ORANG DENGAN MEMPERTIMBANGKAN FAKTOR KENYAMANAN - Rachmad Haryyadi (2022)
The sanitary system on ships is an indispensable component in a ship to facilitate the needs of passengers and crew in the clean water distribution system and for sanitary or health purposes, the health in question is for the purposes of washing hands, kitchen needs, bathing and so on. There are often problems in the sanitary system such as blockages in the pipes and inconvenience for passengers when using these facilities. So a re-design was carried out to maximize the sanitary system on the ship and provide comfort to passengers and crew. From the results of the redesign, it is concluded that economically the use of the new design can increase the total cost because there is a complete change of material in the pipes and the addition of sewage tanks. The suggestion that can be given is that the redesign is carried out on ships that have a larger passenger capacity, so that they can find new problems and can be used as lessons in the world of shipping. Keywords : Re-design, Sanitary System, Passenger Ship